Exploring genetic determinants of antimicrobial resistance in Brucella melitensis strains of human and animal origin from India - Ayoub, Haris; Kumar, M. Suman; Mehta, Rishabh; Thomas, Prasad; Dubey, Muskan; Dhanze, Himani; Ajantha, Ganavalli S.; Bhilegaonkar, K. N.; Salih, Harith M.; Cull, Charley A.; Veeranna, Ravindra P.; Amachawadi, Raghavendra G. (Frontiers in Microbiology, 2024)
Antimicrobial resistance (AMR) in Brucella melitensis, the causative agent of brucellosis, is of growing concern, particularly in low and middle-income countries. This study aimed to explore the genetic basis of AMR in B. melitensis strains from India. Twenty-four isolates from humans and animals were subjected to antimicrobial susceptibility testing and whole-genome sequencing. Resistance to doxycycline (20.80%), ciprofloxacin (16.67%), cotrimoxazole (4.17%), and rifampicin (16.67%) was observed. Genome analysis revealed efflux-related genes like mprF, bepG, bepF, bepC, bepE, and bepD across all isolates, however, classical AMR genes were not detected. Mutations in key AMR-associated genes such as rpoB, gyrA, and folP were identified, intriguingly present in both resistant and susceptible isolates, suggesting a complex genotype-phenotype relationship in AMR among Brucella spp. Additionally, mutations in efflux genes were noted in resistant and some susceptible isolates, indicating their potential role in resistance mechanisms. However, mutations in AMR-associated genes didn't consistently align with phenotypic resistance, suggesting a multifactorial basis for resistance. The study underscores the complexity of AMR in B. melitensis and advocates for a holistic multi-omics approach to fully understand resistance mechanisms. These findings offer valuable insights into genetic markers associated with AMR, guiding future research and treatment strategies.